2021
DOI: 10.2147/ijn.s312752
|View full text |Cite
|
Sign up to set email alerts
|

Chlorambucil-Iron Oxide Nanoparticles as a Drug Delivery System for Leukemia Cancer Cells

Abstract: Introduction: Traditional cancer therapies may have incomplete eradication of cancer or destroy the normal cells. Nanotechnology solves the demerit by a guide in surgical resection of tumors, targeted chemotherapies, selective to cancerous cells, etc. This new technology can reduce the risk to the patient and automatically increased the probability of survival. Toward this goal, novel iron oxide nanoparticles (IONPs) coupled with leukemia anti-cancer drug were prepared and assessed. Methods: The IONPs were pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Chloramb is used as an alkylating agent in the chemotherapy of chronic lymph leukemia (CLL) and chronic myeloid leukemia (CML). CS-IONPs with core-shell structure were prepared by Hussein-Al-Ali et al (2021) Chloramb-CS-IONPs were synthesized by ionic gelation method using CS-IONPs as carriers of chlorambucil with 19% loading rate of chloramb. In this study, Chloramb-loaded IONPs reduced cancer cell viability in a leukemia cell line (WEHI) better than Chloramb.…”
Section: Application Of Iron Nanoparticles In Leukemiamentioning
confidence: 99%
“…Chloramb is used as an alkylating agent in the chemotherapy of chronic lymph leukemia (CLL) and chronic myeloid leukemia (CML). CS-IONPs with core-shell structure were prepared by Hussein-Al-Ali et al (2021) Chloramb-CS-IONPs were synthesized by ionic gelation method using CS-IONPs as carriers of chlorambucil with 19% loading rate of chloramb. In this study, Chloramb-loaded IONPs reduced cancer cell viability in a leukemia cell line (WEHI) better than Chloramb.…”
Section: Application Of Iron Nanoparticles In Leukemiamentioning
confidence: 99%
“…Two bands are produced by the C-Cl bond at 744 and 723 cm À1 . 50 However, the C-H group is considered a characteristic peak of T-80 at 2907 and 2855 cm À1 , the ester (CQO) group is stretched at 1735 cm À1 , and the OH group produces a strong band at 3436 cm À1 . 51 The obtained results of nCH demonstrated that two broad spectrums in the range of 945-1050 cm À1 are due to the hydrogenbonded (O-H) group of CH drug, whereas 1325 and 1445 cm À1 are due to the stretching vibration of the (C-O) group of T-80 and CH drug.…”
Section: Preparation and Characterization Studiesmentioning
confidence: 99%
“…Chlorambucil, another viable candidate for MNP-based delivery, is used for the treatment of chronic lymphocytic leukaemia, as well as both Hodgkin’s and non-Hodgkin’s lymphoma [ 57 , 58 ]. In a recent study, chlorambucil was incorporated into Fe 3 O 4 iron oxide MNPs via a chitosan shell and showed increased efficacy in drug release onto cancer cells, compared to the non-complexed drug [ 59 ]. Another recent investigation with anticancer drug violamycin loaded onto 8–10 nm iron oxide nanoparticles, have shown increased effectiveness against to MCF-7 breast cancer cell line [ 53 , 60 ], indicating the potential in such SPION-based systems in drug delivery.…”
Section: Drug Deliverymentioning
confidence: 99%